Project-based learning untuk meningkatkan berpikir kritis dalam pjok - Cecep Yuli Purnomo; Priambodo, Anung; Setiyo Hartoto (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2025)
Physical Education learning in elementary schools still often focuses solely on motoric aspects, so that strengthening students' cognitive aspects is less than optimal. This study aims to examine the effectiveness of the Project-Based Learning (PjBL) model in improving students' critical thinking skills in PJOK subjects. The method used is quantitative with a pretest-posttest design, involving 33 grade IV students at SDN Sidodadi II Taman, Sidoarjo, who were selected randomly. The instrument in the form of a critical thinking questionnaire was compiled based on five main indicators: formulating problems, analyzing, evaluating, being open to alternatives, and expressing opinions based on facts. The results of the paired sample t-test showed a significant increase (p = 0.000 <0.05) after the implementation of PjBL. These findings indicate that PjBL is effective in encouraging active involvement, collaboration, and analytical thinking of students in PJOK learning.